Illegal transactions in international trade : theory and measurement - Bhagwati, Jagdish N.,ed (Amsterdam ; New York : North-Holland ; American Elsevier, 1974)
This book first elaborates on a theoretical analysis of smuggling, an alternative proof of the Bhagwati-Hansen results on smuggling and welfare, and smuggling and trade policy. Discussions focus on optimal tariff and revenue questions, legal trade eliminated by smuggling, legal trade co-existing with smuggling, overinvoicing and underinvoicing of transactions, and smuggling and welfare. The text then examines overinvoicing, underutilization, and distorted industrial growth, fiscal policies, faking of foreign trade declarations, and the balance of payments, and accuracy of economic observations. Topics include statistics of foreign commodity trade, trade tariffs and subsidies, effect on capital complexity, industrial employment and output growth, implications for industrial development, effective exchange rate for capital imports, and foreign-exchange profits of overinvoicing.
Includes index.
kjo 17/01/2019
Loans
Keywords: International trade; Smuggling; Invoices; Commercial statistics